Empowerment the An-Nadzir Community in South Sulawesi: An Islamic Communication-Social Capital-Economic Action Model - Tike, Arifuddin; Tajibu , Kamaluddin; Fahlevi, Akhmad Fathur (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2026)
This study aims to analyze the role of Islamic communication in building productive social capital and empowering the economy of the An-Nadhir Muslim minority community in Romanglompoa, South Sulawesi. Using a qualitative approach with ethnographic strategies and grounded theory analysis over 30 days, this study developed the Islamic Communication-Social Capital-Economic Action (ICSEA) Model, which explains the mechanisms of transforming religious values ​​into collective economic action. Data was obtained through observation, in-depth interviews and document studies, documents were analyzed using NVivo 15. This study concludes that the An-Nadzir community in Romanglompoa, Gowa Regency, South Sulawesi, represents a unique phenomenon in how Islamic communication practices can transform religious discourse into productive social capital and measurable collective economic action. Despite being located in a Muslim minority context with complex structural challenges, this community has succeeded in developing economic empowerment mechanisms based on Islamic values ​​that demonstrate high resilience and adaptability. The ICSEA model was developed to explain the specific transformation mechanisms occurring in the An-Nadzir community, where communication practices based on hikmah (wisdom), mau'izah hasanah (good deeds), and mujādalah (intelligible texts) create a systematic pathway from religious values ​​to concrete economic empowerment. Thus, Islamic values ​​can act as a catalyst in the context of Islamic communication and social capital for the An-Nadzir community, thereby building religious trust, social networks, and collective efficacy, which are necessary for sustainable economic action.